2015
DOI: 10.15218/zjms.2015.0017
|View full text |Cite
|
Sign up to set email alerts
|

HPLC analysis and antidiabetic effect of Rheum ribes root in type 2 diabetic patients

Abstract: Background and objective: Rheum ribes (polygonaceae) roots are used traditionally to treat diabetes, hypertension, obesity, ulcer, diarrhea, anthelmintic and expectorant. The purpose of this study was to investigate clinically the antidiabetic activity of Rheum ribes in type 2 diabetes mellitus patients and phytochemical study for the correlation of antidiabetic activity with the active constituents in the plant. Methods: The antidiabetic activity of Rheumribes given alone and in combination with standard oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…[17,19] Multiple studies have shown that R. Ribes roots have antidiabetic activity, including antihyperglycemic, insulin-releasing, and antiretinopathic activities. [20][21][22][23] Urtica Dioica (U. Dioica) is another medicinal plant, which belongs to the Urticaceae family. This plant is also famous for its use as a food ingredient and herbal drug.…”
Section: Introductionmentioning
confidence: 99%
“…[17,19] Multiple studies have shown that R. Ribes roots have antidiabetic activity, including antihyperglycemic, insulin-releasing, and antiretinopathic activities. [20][21][22][23] Urtica Dioica (U. Dioica) is another medicinal plant, which belongs to the Urticaceae family. This plant is also famous for its use as a food ingredient and herbal drug.…”
Section: Introductionmentioning
confidence: 99%
“…Four hundred grams of dried powdered leaves and seeds of M. oleifera were extracted through 1 L ethanol (Chem-Lab, Belgium) using an ultrasonic-assisted extractor (LUC-405, Korea) for 1hr at 40°C. After filtration and drying, the extract was redissolved in 10% ethanol and fractionated by diethyl ether (Chem-Lab, Belgium), and ethyl acetate (Chem-Lab, Belgium) [19,20]. The obtained fractions were stored at 4°C until their usage for phytochemical screening and evaluation of their biological activity.…”
Section: Plant Collection and Extract Preparationmentioning
confidence: 99%
“…Only Rheum ribes L. is naturally occurring in Turkey (Tosun and Kizilay, 2003) and it has also found in Iran, Pakistan, Afghanistan, Iraq, Armenia and Lebanon (Bazzaz et al, 2005;Ekincialp et al, 2019). It is perennial plant and its flower stalks are consumed as vegetables (Naemi et al, 2014); it could be used as a medicine for diabetes, root parts help to reduce glucose in the blood especially in type 2 diabetes (Raafat et al, 2014;Adham and Naqishbandi, 2015;Raafat and El-Lakany, 2018); and it has been reported as an effective herb in studies for diseases such as diarrhea, cancer, and Alzheimer's (Zahedi et al, 2015;Khiveh et al, 2017;Aygün et al, 2020).…”
Section: Introductionmentioning
confidence: 99%